Birth and death : experience, ethics, politics - Woodward, Kath; Woodward, Sophie (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Usually conceived in opposition to each other - birth as a hopeful beginning, death as an ending - this book brings them into dialogue with each other to argue that both are central to our experiences of being in the world and part of living. Written by two authors, this book takes an intergenerational approach to highlight the connections and disconnections between birth and death; adopting a relational approach allows the book to explore birth and death through the key relationships that constitute them: personal and social, private and public, the affective and social norms, the actual and the virtual and the ordinary and profound. Of interest to academics and students in the fields of feminism, phenomenology and the life course, the book will also be of relevance to policy makers in the areas of birth activism and end of life care. Drawing from personal stories and everyday life and publicly contested examples the book will also be of interest to a more general readership as it engages with questions we all at some point will grapple with"--
Sheila Kitzinger: a life in birth and a good death -- Personal and social -- Visibility and visualisation -- Public and private: rituals and routines -- The medical and the natural: embodied selves -- Crossing boundaries: ethics and experience -- Giving birth, dying and mostly, living
OCLC-licensed vendor bibliographic record.
Keywords: Life cycle, Human -- Social aspects; Childbirth -- Social aspects; Death -- Social aspects; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General